Enhanced microalgal lipid production with media engineering of potassium nitrate as a nitrogen source. Issue 1 (1st January 2018) - Gour, Rakesh Singh; Bairagi, Madhusudan; Garlapati, Vijay Kumar; Kant, Anil
ABSTRACT: Algal biofuels are far from a commercial reality due to the technical challenges associated with their growth and lipid extraction procedures. In this study, we investigated the effect of 4 different media and 5 different nitrogen sources at 5 levels on the growth, biomass and lipid productivity of Scenedesmus sp and Chlorella sp The hypothesis was that a nitrogen source can be identified that provides enough stress to accumulate lipids without compromising significantly on biomass and lipid productivity. A maximum specific growth rate and doubling per day have been observed with algal species using modified BG-11 medium. Among the tested nitrogen sources, 2.5 mM potassium nitrate as a nitrogen constituent of modified BG-11 medium resulted in higher lipid content and productivity in the case of S. dimorphus (29.15%, 15.449 mg L −1 day −1 ). Another noteworthy outcome of the present study lies in the usage of a smaller amount of the nitrogen source, i.e., 2.5 mM, which is found to be 7 times less than the standard BG11 media (17.60 mM sodium nitrate).